Research on TR-STBC Coding Technology in Shortwave MIMO Channels - Luo, Xiaobao; Lin, Jian; Cheng, Weiheng; Gao, Yunxiang; Chen, Liukui (2023 International Conference on Networks, Communications and Intelligent Computing (NCIC), 2023)
In response to the challenges of narrow bandwidth, susceptibility to interference, and poor stability in shortwave communication, this study investigates the application of MIMO (Multiple Input Multiple Output) technology to the shortwave communication system. To address symbol interference arising from multipath effects, a time reversal operation is introduced, involving temporal inversion and complex conjugation of the signal. At the receiving end, matched filtering decoding is employed, resulting in a reliable and efficient 2×2 shortwave MIMO channel model. Through simulation validation, it has been demonstrated that time-reversed space-time coding can effectively enhance the system's bit error rate performance.